Constructing “Nobility” around a Later-Married Wife: Natal-Family Meaning-Making under Charismatic Religious Authority in Indonesia - Nugraha, Yuda Agung; Iqbal, Asep Munawar (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
Polygyny remains a contested religious and social practice in Indonesia, but research has rarely examined how a wife’s natal family participates in legitimizing a subsequent marriage. This article examines how a later-married wife and her natal family constructed “nobility” as a counter-narrative to stigma and how the charismatic authority of a kiai (Muslim religious leader) mediated their reception of Qur’an 4:3. The analysis draws on an interpretive qualitative single-case study conducted from January through early July 2026 in an anonymized Islamic study-circle community in West Java. Data were collected through participant observation and in-depth interviews with the wife, three members of her natal family, and three external informants. The material was coded manually and iteratively, then interpreted through the Living Qur’an perspective and Berger and Luckmann’s social constructionist framework of externalization, objectivation, and internalization. The findings show that “nobility” was externalized through material provision, redistribution, giving practices, and domestic hierarchy; objectivated through repeated narratives about religious knowledge, household provision, and social influence; and internalized through marital reasoning, forms of address, spatial conduct, and deference to religious authority. The family’s reception of Qur’an 4:3 was mediated primarily through accounts of the kiai’s biography rather than an observed formal exegesis of the verse. External informants questioned his marital conduct, the meaning of consent, and whether material prosperity constituted blessing. The case therefore shows that the natal family actively participated in producing marital legitimacy, although this construction remained contextual and contested rather than theologically conclusive or uniformly accepted.